2021
DOI: 10.1111/ajt.16093
|View full text |Cite
|
Sign up to set email alerts
|

Significance of revised criteria for chronic active T cell–mediated rejection in the 2017 Banff classification: Surveillance by 1-year protocol biopsies for kidney transplantation

Abstract: Diagnostic criteria for chronic active T cell-mediated rejection (CA-TCMR) were revised in the Banff 2017 consensus, but it is unknown whether the new criteria predict graft prognosis of kidney transplantation. We enrolled 406 kidney allograft recipients who underwent a 1-year protocol biopsy (PB) and investigated the diagnostic significance of Banff 2017. Interobserver reproducibility of the 3 diagnosticians showed a substantial agreement rate of 0.68 in Fleiss's kappa coefficient. Thirty-three patients (8%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…VL Kung et al: CA TCMR is variably responsive to treatment treated because of lack of evidence on treatment efficacy. 26,27 As a center that has diagnosed CA TCMR since its inclusion in the Banff classification but does not treat patients with this diagnosis in a uniform manner, we show, in an albeit small cohort of only 44 treated, pure CA TCMR cases without ABMR or intimal arteritis, a 20% response rate (9 of 44 with $50% eGFR recovery at 4 weeks after biopsy) to immunosuppressive therapy. This preliminary finding supports the notion that increased immunosuppression might be efficacious in a subset of CA TCMR cases.…”
Section: Discussionmentioning
confidence: 82%
“…VL Kung et al: CA TCMR is variably responsive to treatment treated because of lack of evidence on treatment efficacy. 26,27 As a center that has diagnosed CA TCMR since its inclusion in the Banff classification but does not treat patients with this diagnosis in a uniform manner, we show, in an albeit small cohort of only 44 treated, pure CA TCMR cases without ABMR or intimal arteritis, a 20% response rate (9 of 44 with $50% eGFR recovery at 4 weeks after biopsy) to immunosuppressive therapy. This preliminary finding supports the notion that increased immunosuppression might be efficacious in a subset of CA TCMR cases.…”
Section: Discussionmentioning
confidence: 82%
“…In protocol biopsies performed at 1 year, Nakagawa et al demonstrated a low number of cases with CA-TCMR grade I (28/406 = 6.9%) with 22 of these 28 cases also meeting criteria for acute TCMR or borderline. 2 In support of the concept of CA-TCMR its diagnosis was associated with tubulitis in IFTA, evolved from smoldering inflammation below Banff thresholds for acute rejection (i.e., borderline) and was associated with increased risk of graft failure, independent of ABMR.…”
Section: Does the Definition Of Chronic Active T Cell-mediated Rejection Need Revisiting?mentioning
confidence: 92%
“…The Banff 2017 report explicitly states that further studies on this newly defined Banff category were necessary. 1 In response, several recent studies, 2,3 and that of Helgeson et al in the current issue of AJT, 4 have evaluated the phenotype of CA-TCMR in more detail in large, well-annotated cohorts.…”
Section: Does the Definition Of Chronic Active T Cell-mediated Rejection Need Revisiting?mentioning
confidence: 99%
“…The prognosis for allograft survival with a diagnosis of CA‐TCMR is considered poor. Our previous study 3 reported that the revised criteria from Banff 2015 to 2017 increased the incidence of CA‐TCMR by 1‐year protocol biopsy from 1% to 8%. In addition, the revised CA‐TCMR criteria were associated with a 5.42‐fold risk of a composite endpoint defined as a two‐fold increase in serum creatinine compared with the level in normal tissue or censored allograft loss and indicated that CA‐TCMR is the second poorest graft prognostic diagnosis after antibody‐mediated rejection.…”
Section: Introductionmentioning
confidence: 99%